2019
DOI: 10.1007/s00216-019-02263-6
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of perfluoroalkyl substances and bile acids in human serum using ultra-high-performance liquid chromatography–tandem mass spectrometry

Abstract: There is evidence of a positive association between per-and polyfluoroalkyl substances (PFASs) and cholesterol levels in human plasma, which may be due to common reabsorption of PFASs and bile acids (BAs) in the gut. Here we report development and validation of a method that allows simultaneous, quantitative determination of PFASs and BAs in plasma, using 150 μL or 20 μL of sample. The method involves protein precipitation using 96-well plates. The instrumental analysis was performed with ultraperformance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 31 publications
(48 reference statements)
3
45
0
Order By: Relevance
“…The comparison of serum lipid levels between the exposed and control areas was based only on water districts, not serum PFAS levels. Therefore, it is not affected by potential confounding related to intestinal reabsorption of PFAS and bile acids [15,16]. However, the participants from the two areas may differ in other aspects than water quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of serum lipid levels between the exposed and control areas was based only on water districts, not serum PFAS levels. Therefore, it is not affected by potential confounding related to intestinal reabsorption of PFAS and bile acids [15,16]. However, the participants from the two areas may differ in other aspects than water quality.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of potential confounding by dietary factors, or reverse causality (by binding of PFAS to lipoproteins), was discussed extensively by EFSA [7]. Moreover, confounding by variability in intestinal reabsorption of PFAS and bile acids, which in turn is associated with serum cholesterol, remains an important issue when exposure to PFAS is assessed by serum PFAS levels [15,16]. PFAS are excreted in bile, but reabsorbed in the intestine to a high extent, and relatively high reabsorption should be associated with higher steady state PFAS levels in serum.…”
Section: Introductionmentioning
confidence: 99%
“…The relative low sensitivity is a possible limitation of this approach. Recently published methods providing concentration of samples by nitrogen-drying achieved detection limit below 1 ng/mL for most BA, which is >10-fold lower than the LOQ that can be achieved with our assay [30]. However, due to the purpose of obtaining a suitable method for future clinical studies, sensitivity has been outweighed by fast and high throughput analyses.…”
Section: Discussionmentioning
confidence: 73%
“…Conversely, a more recent investigation, including 20 healthy individuals [11], found that the median values of most BA were higher than those observed in our study. Nonetheless, this difference could be attributable to the different age of the population, which has not been clearly reported in the previous investigation of Salihović et al [30]. Along with the validation procedure and establishment of reference ranges, we also performed interference studies aimed at assessing the matrix effect from in vitro hemolysis, lipemia, and hyper-bilirubinaemia.…”
Section: Discussionmentioning
confidence: 97%
“…coupled to a triple quadrupole mass spectrometer as previously described. 22 Briefly, all For statistical analyses of PFAS and BA concentrations, the data was zero imputed, log2…”
Section: Analysis Of Bas and Pfasmentioning
confidence: 99%